Pluralism-Based Law Enforcement in the Handling of Baduy Customary Criminal Cases by the Lebak District Prosecutor’s Office, Banten - Jefri Penanging Makapedua; Merry Elisabeth Kalalo; Dani Robert Pinasang; Caecilia Johanna Julietta Waha (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
The constitutional recognition of customary law community units in Article 18B paragraph (2) of the 1945 Constitution demands criminal law enforcement that is not purely positivistic, but rather respects the living law within society. This study examines pluralism-based law enforcement in the handling of customary criminal cases of the Baduy community by the Lebak District Prosecutor’s Office, Banten, with the aim of analyzing the philosophical foundation, the implementation, and the ideal concept of the prosecutorial function in integrating customary law with state law. The method employed is normative legal research supported by an empirical field study, through statutory, conceptual, and socio-legal approaches, as well as descriptive-analytical qualitative analysis. The results show that the Lebak District Prosecutor’s Office positions Baduy customary law as a normative system on an equal footing with state law and shifts the retributive paradigm toward a restorative one through Prosecutor’s Regulation Number 15 of 2020. The handling mechanism operates through pre-prosecution filtering, coordination with the Puun and the Jaro, and the absorption of customary decisions as the basis for the termination of prosecution as well as a mitigating factor in the indictment. The ideal concept positions the prosecutor as a facilitator of legal pluralism who bridges the interests of the state and the customary community. The study concludes that specific regulation and a dedicated unit of prosecutors assisting customary communities are needed so that legal pluralism rests on a strong legal basis and does not remain sporadic.